KORELASI KREATIVITAS GURU DALAM MENGAJAR TERHADAP PRESTASI BELAJAR SISWA SDN 25 DOMPU - Mulya Yusnarti; Dedi Kusnadi (Jurnal Pendidikan Dasar Borneo (Judikdas Borneo), 2021)
The study aims to determine correlation between teacher creativity in teaching and learning achievement of students at SDN 25 Dompu. The research method was quantitative research with a sample of 41 students. Data were collected using questionnaires and learning outcomes tests. The questionnaire contains 15 statements and the learning outcome test consists of 20 multiple choice questions. The data analysis technique used inferential statistics. Based on the results of data analysis, teacher creativity in teaching had a significant relationship with student achievement with a t-count of 3.6733 greater than the t-table value of 1.6828 or (3.67331.6828) in accordance with the number n = 41 at the 5% significance level or the level of confidence. 95%. This shows that the null hypothesis (Ho) which says. There is no relationship between teacher creativity in teaching and learning achievement of fourth grade students at SDN 25 Dompu, is rejected, and the alternative hypothesis (Ha) which says  there is a relationship between teacher creativity in teaching with the learning achievement of fourth grade students at SDN 25 Dompu was accepted.